Better Scrum through Essence. (18th January 2022) - Jacobson, Ivar; Sutherland, Jeff; Kerr, Brian; Buhnova, Barbora
Abstract: We live at an exciting time where software has become a dominant aspect of our everyday life. Although software provides opportunities for improving various aspects of our society, it also presents many challenges. One of them is development, deployment, and sustaining of high quality software on a broad scale. While agile methods (Scrum being one of the most prominent examples) ease the process, their popularity deteriorates the clarity and simplicity they were once meant to bring into software development. This article explores the synergy of Scrum and Essence, a domain model of software engineering processes, intending to become a common ground for software development methods, bringing clarity into the composition of methods from individual practices. This short communication motivates the interplay of Scrum and Essence, being accompanied with a set of videotutorials and 21 Scrum Essential cards to further guide more effective team's way of working.